COMPARISON OF PARTICLES SIZE AND PRESSURE OF COCONUT SHELL CHARCOAL BRICKETS ON COMBUSTION TIME AND TEMPERATURE - Mali, Alfin; Crisanto Putra Mbulu, Bernardus; Tugur Redationo, Nereus (Mechanical, Energy and Material (METAL), 2024)
Briquettes are a type of alternative energy whose raw material source comes from agricultural waste such as coconut shells. Coconut shells are converted into charcoal which has a higher calorific value through the pyrolysis process. The aim of this research is to determine the effect of comparing particle size and printing pressure on the length of burning time and burning temperature, so as to obtain a briquette composition that is durable and produces high temperatures. In this research, the raw material used was shell waste with a drying process of 400°C and the particle size variations used were mesh 30, 150 and 250 mixed with 12 grams of starch adhesive. The briquette molding process uses 3 kg and 5 kg pressure, which are then dried using an oven at a temperature of 750°C for 3 hours. Tests were carried out on burning time, burning temperature, water content and ash content. From the research results, it was found that for the highest temperature, briquettes with a particle size of 250 mesh were produced with a pressure of 5 kg at 312°C, and the flame duration of the briquettes was 240 minutes.